Attitudes of individuals in Eastern Turkey toward epilepsy and the factors associated with these attitudes - Turan, Gulcan Bahcecioglu; Aksoy, Meyreme; Ozer, Zulfunaz (Academic Press Inc Elsevier Science, 2021)
Aim: This study was performed to analyze the attitudes of individuals in eastern Turkey toward epilepsy and the factors associated with these attitudes. Methods: Designed as a cross-sectional descriptive study, this study was performed from January 28 to February 8, 2021. A snowball sampling technique was used to select the study sample, and a survey was sent online to individuals aged 18 or above. A total of 617 individuals who filled in this online survey form were included in this research. Data were collected via a personal information form and the Public Attitudes Toward Epilepsy (PATE) scale. Results: The results showed that the mean scores of the participants on the PATE scale, on its general domain, and on its personal domain were 1.79 +/- 0.63, 1.70 +/- 0.63, and 1.96 +/- 0.77, respectively. Comparing the participants' mean PATE scale scores on the basis of their descriptive characteristics revealed statistically significant differences in the mean scores on the scale and its two domains in terms of age, place of residence, educational level, knowing anyone who had epilepsy or experienced epileptic seizures, and witnessing a person having an epileptic seizure (p < 0.05). Conclusion: Individuals living in eastern Turkey have positive attitudes toward epilepsy. Moreover, it was found that, among all the participants, those who were relatively young, those who lived in a provincial center, those who had a relatively high educational level, those who knew an individual with epilepsy, and those who had witnessed an epileptic seizure have more positive attitudes toward epilepsy than their counterparts. Implications: It is recommended to design educational programs focusing on raising the level of public awareness and knowledge regarding epilepsy. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Attitude; Epilepsy; Society